ENTREPRENEURIAL ORIENTATION, DIGITAL TRANSFORMATION, AND INNOVATION IN JAKARTA FASHION MSMEs PERFORMANCE - Keshia Aurelia Agatha; Louis Utama (Graduate Program of Universitas Tarumanagara, 2026)
This research aims to investigate the impact of entrepreneurial orientation and digital transformation on the performance of fashion MSMEs in Jakarta, through innovation as a mediating variable. The background of this study is based on low levels of innovation, limited digital technology adoption, and weak entrepreneurial behavior, which hinder the achievement of optimal business performance. This study employs a quantitative approach involving 185 respondents who are fashion MSME owners. The non-probability sampling technique used is purposive sampling, in which respondents were selected based on the criteria of actively operating their businesses through digital platforms. The collected data were analyzed using Structural Equation Modeling (SEM) to identify the relationships among the variables. The research instruments passed validity and reliability testing, confirming that all indicators were appropriate and reliable for measurement. The findings indicate that entrepreneurial orientation and digital transformation have a positive and significant effect on MSME performance. Both variables contribute positively to Innovation, which functions as a mediator in the relationship between Entrepreneurial Orientation, Digital Transformation, and Business Performance. This study contributes to the field of entrepreneurship by reinforcing the importance of entrepreneurial orientation as a strategic capability that drives innovation and enhances MSME business performance in the digital era. The findings provide empirical evidence that entrepreneurial behavior remains a key determinant of competitiveness for fashion MSMEs operating within increasingly digital business environments.